Caroll Pyramid Implementation of Environmental Responsibility Programs of PT Pertamina EP Subang Field, Tambun Field, and Jatibarang Field in Organic Agriculture - Karijanto Prijo Rahardjo; Kurniawati Kurniawati (International Journal Labs, 2023)
The era of using synthetic chemical fertilizers in agriculture is slowly being abandoned and is now entering the era of organic fertilizers. Against this background, this study aims to: (1) Analyze the implementation of environmental social responsibility programs at PT. Pertamina EP Subang Field, Jatibarang Field, Tambun Field (2) Analyzing the process of implementing environmental social responsibility at PT. Pertamina EP Subang Field, Jatibarang Field, Tambun Field (3) Analyze the implications of behavior related to the implementation of environmental social responsibility at PT. Pertamina EP Subang Field, Jatibarang Field, and Tambun Field in terms of sustainable development responsibilities and social empowerment. This research method uses qualitative methods. The data analysis technique uses the four strategic principles of Carroll's pyramid. The results of the research show that PT Pertamina EP Subang Field, Jatibarang Field, and Tambun Field have and are implementing the four strategic principles of the Carroll pyramid in principle, including economic, legal, ethical, and philanthropic principles. Meanwhile, the managerial implication of this research is the management of PT. Pertamina EP Subang Field, Jatibarang Field, and Tambun Field must continue their responsibilities in these four dimensions. Companies must also continue to provide concrete support for the development of new, renewable energy and energy conservation (EBTKE) through the establishment of Subholding Power & NRE. Companies must continue to strive to change HR behavior, internally and externally, so that social and environmental responsibilities can be carried out together.